Dental fluorosis decline after changes to supplement and toothpaste regimens - Riordan PJ. (Blackwell Synergy, 2002)
In 1989/90, in 659 12-year-olds in Perth (F 0.8mg/L) and the Bunbury region of Western Australia (WA) (F ,0.25mg/L), dental fluorosis prevalences were 40.2% and 33.0%. Fluoride supplements (OR 4.63) and extended residence in a fluoridated area (OR 4.06) were significant risk factors; toothpaste ingestion variables had ORs greater than unity; in 1990, DMFT for this age group was 0.84. School Dental Service took steps to discourage supplement and toothpaste ingestion and to promote low fluoride toothpaste for children , 6years of age.